ENHANCING PERFORMANCE AND ATTITUDES TOWARDS INSTRUCTIONAL PLANNING AMONG HIGHER DIPLOMA SCIENCE TEACHERS USING COGNITIVE APPRENTICESHIP MODE - Abu-Hudra, Suzan Mahmoud (Journal of Educational and Psychological Sciences, 2019)
The focus of the expert interaction in a cognitive apprenticeship is on developing cognitive skills of reflection through discourse and application of knowledge. The propose of this study explanatory a method for enhancing the effectiveness of cognitive apprenticeship theory for improving personal science teaching efficacy beliefs of higher diploma preservice teachers. The research is based on the study of the impact of cognitive apprenticeship in studying science materials. The study involved 22 teachers (20-30 years) enrolled in 14-week Science teaching strategies course in the high general diploma in Science and Humanities College-Jubail, Imam Abdulrahman Bin Faisal University, Saudi Arabia. The instrument contained 23 items and divided into two sub-scales: 13 items measuring personal science teaching efficacy PSTE and 10 items measuring science teaching outcome efficacy STOE. The quantitative findings showed a continuous statistically significant linear increase between before and after course measures of PSTE. However, a slight decrease in their PSTE was observed in the final post-course measure that is a commonly observed long-term effect after many educational interventions. A t-test determined that the decline was not statistically significant, indicating that teaching internship had no significant effect on the preservice teachers' science teaching efficacy beliefs. The study provides a significant evidence to suggest that the preservice teachers perceived that their learning experience in the Science teaching strategies course by cognitive apprenticeship methods was unique when compared to before teaching methods courses taken.
Keywords: cognitive apprenticeship; science teachers; science teaching competency program STOE; STOE